New Inventory of the Russian glaciers based on satellite data (2016–2019) - T. Y. Khromova; G. A. Nosenko; A. F. Glazovsky; A. Y. Muraviev; S. A. Nikitin; I. I. Lavrentiev (Лëд и снег)
The new Inventory of the Russian glaciers has been created at the Institute of Geography of the Russian Academy of Sciences mainly on the basis of the Sentinel 2 satellite images for 2016–2019 with the aim of assessing the current state of glacier systems and as a basis for monitoring and re-inventorying. Delineation of glacier outlines was manually made to reduce uncertainties, especially for small glaciers. The database structure is compatible with the global and national glacier archives and includes the main glacial parameters. Additionally a classification of possible catastrophic phenomena of glacial genesis was developed: dynamically unstable glaciers, glacier lakes, icebergs, etc. The data base is available online (www.glacrus.ru). At present, there are 22 glacial systems in Russia with a total area of 54,518 km2. The largest glacial systems by area are located in the Arctic archipelagos: Novaya Zemlya, Severnaya Zemlya, and Franz Josef Land. The glacial systems of the Caucasus, Kamchatka, and Altai are the largest by area in the continental part of Russia. The main group consists of 13 small glacial systems, the area of which does not exceed 100 km2. They are located in different glaciological zones: from the De Long Islands in the Arctic to the Eastern Sayan in southern Siberia. Since the compilation of the USSR glacier Inventory (1965–1982), the area of glaciers has decreased by 5,594 km2, or 9.3%. The area of polar glaciers has decreased in smaller degree than that of glaciers in mountainous regions. The results of our research confirm the trend of reducing the area of glaciers throughout the Russian territory. The magnitude and rate of changes depend on local climatic and orographic features. The exception is the glaciers of the volcanic regions of Kamchatka, the area of which has increased or remained unchanged.